Prototype of Solar Fuel Monitoring And Security System in Dump Truck Tank Based on SMS Gatway - Sigit Priyambodo; Suwanto Raharjo; Slamet Hani; Gatot Santoso; Emy Setyaningsih; Fariyanto (Engineering And Technology Journal, 2024)
The process of security and monitoring of fuel oil is one of the activities that is often overlooked. Fuel oil is a driver of industry on a large scale. The use of fuel is less controlled, so many people abuse the use of diesel fuel which has a fairly high selling price among the public. , so this research was built by utilizing an Arduino microcontroller, proximity sensor, ultrasonic sensor, LCD and utilizing a cellular network with a GSM module 900 device which can send messages. Through this research a system was obtained that can be used for security and monitoring of diesel fuel in tanks. truck to provide information on the condition of the amount of fuel in the tank whether it is suitable for use or not.